Konsep Dan Implementasi Moderasi Beragama dalam Ruang Digital - Umam, Fuadul; Koestanto, R. Riski Dwi (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
Indonesia, as a multicultural country with various ethnicities, religions and races, faces challenges in maintaining tolerance amidst differences of opinion. The Ministry of Religion prioritizes religious moderation to understand and apply religious teachings in a balanced manner. In the digital era, social media plays an important role in disseminating information. This article discusses the concept of religious moderation and strategies for implementing it in digital media. The aim of the research is to reduce extremism and promote tolerance through religious moderation. The research method uses a mixed approach with digital content analysis and interviews. The research results show that the Ministry of Religion actively promotes religious moderation through educational content on platforms such as YouTube. In conclusion, religious moderation in digital media can strengthen tolerance and harmony in society if supported by good strategy and implementation.